Seasonally derived components of the Canada Basin halocline. Issue 10 (26th May 2017) - Timmermans, Mary‐Louise; Marshall, John; Proshutinsky, Andrey; Scott, Jeffery
Abstract: The Arctic halocline stratification is an important barrier to the transport of deep ocean heat to the underside of sea ice. Surface water in the Chukchi Sea, warmed in summer by solar radiation, ventilates the Canada Basin halocline to create a warm layer below the mixed‐layer base. The year‐round persistence of this layer is shown to be consistent with the seasonal cycle of halocline ventilation. We present hydrographic observations and model results to show how Chukchi Sea density outcrops migrate seasonally as surface fluxes modify salinity and temperature. This migration is such that in winter, isopycnals bounding the warm halocline are blocked from ventilation, while the cool, relatively salty and deeper halocline layers are ventilated. In this way, the warm halocline is isolated by stratification (both vertically and laterally) each winter. Results shed light on the fate and impact to sea ice of the warm halocline under future freshening and warming of the surface Arctic Ocean. Key Points: The structure of the Canada Basin halocline is examined in context with its seasonal ventilation by Chukchi Sea waters We show how surface Chukchi Sea water is transferred by subduction into the halocline We demonstrate how the warm halocline is preserved year round because it is isolated by stratification (vertically and laterally) in winter